Annual mean and mean summer/winter air temperature at weather station Vladivostok - Alexander Alatortsev; Anatolii S Astakhov; Valeriy V Babich; Andrey V Darin; Kirill Aksentov; Valentina Sattarova; Ivan S Kirichenko; Alexandr Kolesnik; Mikhail Melgunov; Vladimir Ponomarev (PANGAEA, 2025)
Sediment core LV66-3 (43°07,473 extquotesingle N,131°49,622 extquotesingle E length of 466 cm; water depth 33 m) was collected in 2014 during the 66th cruise of the R/V Akademik M.A. Lavrentiev in the Amur Bay of the Sea of Japan using a gravity core. The sampling location was chosen in the zone of maximum bottom water hypoxia (Tishchenko et al., 2011), which ensured minimal bioturbation of sediments due to oppression of benthic fauna. Continuous seismic profiling data at this site revealed a homogeneous structure of the sedimentary strata, with no visible breaks in sedimentation and no inclusions of sediments of a different composition (Karnaukh et al., 2016). The sediments of core LV66-3 are represented by monotonous clays and silty clays of black or dark gray color without visible stratification, with slightly varying density and humidity (Akulichev et al., 2015; Karnaukh et al., 2016). The analysis of the prepared samples was performed in the Budker Institute of Nuclear Physics (Novosibirsk) using a scanning X-ray fluorescence analyzer with the synchrotron radiation (XRF SR ) at the VEPP-3 storage ring as the excitation source according to previously developed methods (Darin et al., 2005; 2015; Kalugin et al., 2007; 2015). The scanning step was 0.5-0.8 mm. The concentrations of Ca, K, Ti, Mn, Fe, V, Cr, Ni, Cu, Zn, Mo, Pb, Rb, Ba, Sr, Y, Br, As, and Nb were determined. The detection limits for the elements were (mg/g): 0.5 (Br, Rb, Sr, Nb), 1 (Zr, Y), 2 (Zn, Ni, Mn, Pb), 10 (Fe), 15 (Ti), and 100 (Ca, K) (Kalugin et al., 2015). Rubidium-normalized elements were used for dimensionless variation. The age model of core LV66-3 was based on radiocarbon dates, tephrochronological data, and chemostratigraphy. Calibration of the 14C dates to obtain the calendar age of the studied samples was performed with the Calib program (Stuiver and Reimer, 1993) using the Marine13 calibration curve (Reimer et al., 2013). Correction of the reservoir effect was made using the dating of shells from Novik Bay in the eastern part of the Amur Bay (Kuzmin et al., 2001). Geochemical time-series were created using a methodology previously developed for Siberian lakes (Kalugin et al., 2007; 2013; Darin et al., 2005; 2015; Hildebrandt wet al., 2015; Babich et al., 2015; Rudaya et al., 2016) based on the results of XRF SR scanning of the core in the 0-466 cm interval and its age model with some additions that have been used in paleoreconstructions of shelf sediments in the Arctic seas (Astakhov et al., 2019; 2020; 2023). Considering the feature accumulation of sediment in the Amur Bay (Tishchenko et al., 2006; 2011, Akulichev et al., 2016;, Kalugin et al., 2015) and the experience construction of transfer geochemical functions for other areas (Kalugin et al., 2005; 2013; Babich et al., 1980; 2023; Astakhov et al., 2019; 2023), some elements were removed from the initial feature space: Zr, Nb, and Y are significantly enriched in the tephra of the Baitoushan volcano and overlying sediments, molybdenum is the element with maximum response to redox conditions, lead and zinc are possible anthropogenic contaminants in the surface sediment layer (Kalugin et al., 2015), and elements with very low content and weak variability.
In: Alatortsev, A et al. (2025): Geochemical data of the Late Holocene sediments core LV66-3 (Amur Bay of the Sea of Japan) and results of air temperature and precipitation reconstructions for summer and winter by transfer functions [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.987511